An Experimental Comparison of Three Methods for Collision Handling in Virtual Environments - Jacobson, Jeffrey; Lewis, Michael (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 1997)
This study compares three common strategies for handling collisions between the user's virtual body and other objects in a cluttered virtual environment. Test subjects sought “treasures” in a maze of narrow corridors which were embedded in a jumble of irrelevant shapes. The application ran on a PC, with the mouse and screen as the interface. When encounters an object, he either passes through it, stops completely, or is deflected around it. Data show that the third strategy best facilitates goal-seeking behavior with this interface and for this type of problem. This result is significant because collision handling is critically important to the usefulness of Virtual Reality applications. Furthermore, the screen-and-mouse interface is both the most common and least studied for virtual environments.